1989
DOI: 10.1002/anr.1780321106
|View full text |Cite
|
Sign up to set email alerts
|

Differences in responses of normal and rheumatoid arthritis peripheral blood t cells to synovial fluid and peripheral blood dendritic cells in allogeneic mixed leukocyte reactions

Abstract: We examined the response of normal T cells to dendritic cells isolated from the synovial fluid (SF) of patients with either rheumatoid arthritis (RA) or seronegative spondylarthropathies (rheumatoid variants) and to dendritic cells from normal and RA peripheral blood (PB) in the allogeneic mixed leukocyte reaction. Despite the differences in the response kinetics, the stimulatory capacity of SF dendritic cells was similar to that of PB dendritic cells in a 7‐day mixed leukocyte reaction. We also tested the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
See 1 more Smart Citation
“…DC have been identified in rheumatoid ST and SF by several groups over the last 15 years, and elucidation of their derivation, function, and potential role in the pathogenesis of the disease is increasingly better understood [1,2,[9][10][11][12][13][14][15][16][17][18][19][20]. Myeloid DC can be identified and freshly purified from normal or RA peripheral blood (PB), RA SF, or ST cell suspensions through the use of a combination of myeloid markers, and it is therefore possible to directly compare the phenotype and function of PB and SF DC.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…CD33 ϩ CD14 Ϫ CD3 Ϫ CD19 Ϫ CD16 Ϫ myeloid DC were found to be three-to fourfold enriched in fresh SF or ST compared with PB [17]. Synovial myeloid DC were more differentiated than DC precursors that had been freshly purified from either normal or RA PB as demonstrated by MHC class II and adhesion molecule expression [12,17]. SF DC and PB DC stimulated resting allogeneic T cells with equivalent efficacy, and more efficiently than SF monocytes.…”
Section: In Rheumatoid Synoviummentioning
confidence: 99%
“…Subsequent work by two independent groups, led by Jacob Natvig and Nathan Zvaifler, confirmed and extended these observations (57)(58)(59)(60)(61)(62)(63)(64)(65). These studies showed that 1) DC could be readily identified and isolated from synovial fluid as well as tissue, and accounted for 5-7% of RA synovial fluid mononuclear cells; 2) T cells formed clusters around individual synovial DC; 3) synovial DC stimulated T cell responses more potently than did monocytes, in both allogeneic and autologous mixed lymphocyte reactions; 4) functions of synovial DC depended on Class II MHC and included induction of T cell responses to a variety of nominal antigens; 5) adhesion of T cells to DC depended, in part, on interaction of CD2 on the T cell with CD2 ligands on DC; and 6) DC could be found in synovial fluids of patients with inflammatory arthritides other than RA.…”
Section: Identification and Characterization Of Dendritic Cells In Rh...mentioning
confidence: 80%